Is There a Difference between Cemented and Uncemented Femoral Stem Extensions in Revision Knee Arthroplasty? - Lachiewicz, Paul F.; O'Dell, Jane Ann (The Journal of Knee Surgery, 2020)
A stem is usually recommended for the femoral component in revision total knee arthroplasty (TKA) for reasons of alignment, fixation, and bone loss. However, the optimal method of fixation for the femoral component stem remains controversial. We queried the prospective revision TKA database of one surgeon and performed a clinical and radiographic evaluation of 84 knee revisions in which a femoral component stem extension was implanted. There was no established protocol for fixation of the femoral stem during this time. There were 34 knees with cemented (C) fixation and 50 with uncemented (UC) fixation. There were no significant differences in age, gender, body mass index (BMI), or Anderson's Orthopaedic Research Institute (AORI) defect between the two groups. Patients were evaluated using the classic Knee Society clinical and radiographic scores and followed for a mean of 6 years (range: 2–17 years). There was no statistically significant difference in prevalence of reoperation for loosening between cemented and uncemented stems (cemented 3.3% vs. uncemented 10%; p = 0.4). Post hoc power analysis showed that 203 knees in each group would be needed for statistical significance. With the numbers available, there was no difference in aseptic component loosening and radiographic loosening combined (one revision and two radiographic loosening, 9%, in the C group vs. five revisions and three radiographic loosening, 16%, in the UC group; p = 0.51). There was no difference between the groups in the overall rate of any reoperation. There were no differences in postoperative Knee Society pain score, change in pain score, Knee Society function score, or change in function score. Due to the numbers required, a large multicenter study will be needed to determine the optimal method of fixation of the femoral stem in revision TKA.
Keywords: total knee arthroplasty; revision knee arthroplasty; femoral stem; revision techniques; diaphyseal fixation